Are Polycentric Cities More Energy-Efficient? - Schwarze, Björn; Spiekermann, Klaus; Wegener, Michael (Lit, 2020)
The project presented in this paper is part of a four-year program, the Mercator Foundation launched in the municipalities of the Ruhr Region to build awareness of the need for the energy transition and the associated challenges. In it, a computer simulation model of urban land use, transport and environment developed at the Institute of Spatial Planning of the University of Dortmund is being expanded and applied to assess the impacts of land use, transport and other policies in reducing energy consumption and promoting the transition to renewable energy on economy, mobility, quality of life and environment in the Ruhr Region. For this, the model is being augmented by submodels of renewable energy and energy efficiency of buildings. The model will be used to simulate scenarios of future energy price increases and possible combinations of measures to reduce fossil energy consumption and to increase energy efficiency and renewable energy use, in order to achieve the energy policy targets of the German Federal Government. This paper presents initial results of the transport submodel of the integrated model and investigates whether the commonly held hypothesis is correct that polycentric cities are more energy-efficient with respect to mobility than monocentric or dispersed urban regions.
Keywords: Polyzentralität; Raumstruktur; Energieeffizienz; Verkehrssektor; Vergleich; Computersimulation; Dezentralität